2019
DOI: 10.1016/j.chemosphere.2019.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Apex marine predators and ocean health: Proactive screening of halogenated organic contaminants reveals ecosystem indicator species

Abstract: Despite decades-long bans on the production and use of certain chemicals, many halogenated organic compounds (HOCs) are persistent and can bioaccumulate in the marine environment with the potential to cause physiological harm to marine fauna. Highly lipid-rich tissue (e.g., marine mammal blubber) functions as a reservoir for HOCs, and selecting ideal indicator species is a priority for retrospective and proactive screening efforts. We selected five marine mammal species as possible indicators for the Southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…Several comprehensive studies on AHSs and HNPs have been conducted recently. Many have focused on dolphin species in warm water environments because dolphins are considered suitable top consumer species for biomonitoring and HNPs are abundant in such waters [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several comprehensive studies on AHSs and HNPs have been conducted recently. Many have focused on dolphin species in warm water environments because dolphins are considered suitable top consumer species for biomonitoring and HNPs are abundant in such waters [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two years later, Mackintosh et al [ 39 ] identified 45 bioaccumulative DDT-related compounds in blubber from the same species. In 2019, Cossaboon et al [ 36 ] reported a total of 194 halogenated contaminants in the blubber of five marine mammals (long-beaked common dolphin, short-beaked common dolphin, Risso’s dolphin, California sea lion, and Pacific harbor seal) from the Southern California Bight, including 30 HNPs. Most of the compounds (ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many species perform critical roles in structuring biological communities through predation by exhibiting top-down controls thus allowing lower trophic levels to maintain viable diversity [10,11]. As such, the presence, abundance and health of such predators have been used as indicators of the overall health of ecosystems [10,12,13]. In addition, indirect effects of predators can be observed through prey response to the predators [14].…”
mentioning
confidence: 99%